2013
DOI: 10.1016/j.euroneuro.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic activity in Tourette syndrome and obsessive-compulsive disorder

Abstract: Tourette syndrome (TS) and obsessive-compulsive disorder (OCD) both are neuropsychiatric disorders associated with abnormalities in dopamine neurotransmission. Aims of this study were to quantify striatal D2/3 receptor availability in TS and OCD, and to examine dopamine release and symptom severity changes in both disorders following amphetamine challenge. Changes in [(11)C]raclopride binding potential (BP(ND)) were assessed using positron emission tomography before and after administration of d-amphetamine (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 45 publications
3
87
1
3
Order By: Relevance
“…54 With regard to the dopaminergic system, studies have shown contradictory results. Decreased dopamine receptor binding was found in patients with TS (both striatal 61 and extrastriatal 62 ). Steeves et al 62 has found reductions in dopamine receptor binding in the frontal cortex and thalamus.…”
Section: Petmentioning
confidence: 99%
See 1 more Smart Citation
“…54 With regard to the dopaminergic system, studies have shown contradictory results. Decreased dopamine receptor binding was found in patients with TS (both striatal 61 and extrastriatal 62 ). Steeves et al 62 has found reductions in dopamine receptor binding in the frontal cortex and thalamus.…”
Section: Petmentioning
confidence: 99%
“…33 In an MRS study, it was shown that the GABA concentration in SM1 correlated negatively with motor tic severity. 53 Amphetamineinduced dopamin release in the ventral striatum was related to increased tic severity in one PET study, 61 while another PET study did not find any correlations between the TS-related metabolic covariance pattern (with increased activity bilaterally in premotor cortex and cerebellum, associated with relative reductions in striatum and orbitofrontal cortices) and severity of tics. 58 During voluntary movement control measured with MEG, larger amplitudes were inversely correlated with motor tic frequency and severity, 39 while another MEG study found ipsilateral motor cortical inhibition to be inversely related with tic severity.…”
Section: Neuroimaging and Severity Of Ticsmentioning
confidence: 99%
“…The defining symptoms of TS are motor and phonic tics, defined as sudden, repetitive, nonrhythmic, involuntary or semiinvoluntary movements or utterances that involve discrete muscle groups. Tics fluctuate and are exacerbated by stress (3)(4)(5) and by acute challenge with prodopaminergic drugs (6). Individuals with TS also often have deficits in fine motor control (7,8), procedural learning (9), and sensorimotor gating (10,11).…”
mentioning
confidence: 99%
“…Atypical antipsychotics and dopaminergic agents can reduce or exacerbate OCD symptoms, respectively (Bokor and Anderson, 2014). The few reports on DA receptor binding in OCD consistently show decreased DA receptor availability (Denys et al, 2013, Perani et al, 2008 supporting the hypothesis of chronically increased dopaminergic activity in the disorder, which has been recently observed in different brain regions including left and right cerebellum of OCD patients (Hsieh et al, 2014).…”
Section: Discussionmentioning
confidence: 96%